Hormonal regulation of secondary cell wall formation - Didi, Vojtěch; Jackson, Phil; Hejátko, Jan (Journal of experimental botany, 2015)
Secondary cell walls (SCWs) have critical functional importance but also constitute a high proportion of the plant biomass and have high application potential. This is true mainly for the lignocellulosic constituents of the SCWs in xylem vessels and fibres, which form a structured layer between the plasma membrane and the primary cell wall (PCW). Specific patterning of the SCW thickenings contributes to the mechanical properties of the different xylem cell types, providing the plant with mechanical support and facilitating the transport of solutes via vessels. In the last decade, our knowledge of the basic molecular mechanisms controlling SCW formation has increased substantially. Several members of the multi-layered regulatory cascade participating in the initiation and transcriptional regulation of SCW formation have been described, and the first cellular components determining the pattern of SCW at the subcellular resolution are being uncovered. The essential regulatory role of phytohormones in xylem development is well known and the molecular mechanisms that link hormonal signals to SCW formation are emerging. Here, we review recent knowledge about the role of individual plant hormones and hormonal crosstalk in the control over the regulatory cascades guiding SCW formation and patterning. Based on the analogy between many of the mechanisms operating during PCW and SCW formation, recently identified mechanisms underlying the hormonal control of PCW remodelling are discussed as potentially novel mechanisms mediating hormonal regulatory inputs in SCW formation.
Keywords: cellulose; secondary cell wall formation; plant development; plant hormones; cytokinin; lignin; hemicellulose; regulátory růstu rostlin; signální transdukce; Auxin; xylem vessels and fibres.; buněčná stěna; Cell Wall; Plant Physiological Phenomena; fyziologie rostlin; Plant Growth Regulators; Signal Transduction